INFILTRATIVE CARDIOVASCULARDISEASES: CARDIOMYOPATHIES THAT LOOK ALIKE - J.B. Seward; G. Casclang-Verzosa; N. S. Chipigina (Столичная издательская компания, 2016)
Infiltrative CardiovascularDiseases: Cardiomyopathies that look alike.